PEMUTUSAN HUBUNGAN KERJA SECARA SEPIHAK (Studi Kasus Putusan Mahkamah Agung Nomor. 26 K/Pdt.Sus-PHI/2019) (Lex Jurnalica, 2020)
Termination of Employment is the most common cause in Industrial Relations Disputes. Regarding Industrial Relations Disputes regulated in Act Number 2 of 2004 concerning Industrial Relations Disputes Settlement. With the enactment of Law No. 2 of 2004, provides a clear position regarding disputes arising in Industrial Relations. Settlement of disputes arising in Industrial Relations according to Law No. 2 of 2004 can be done in 2 (two) ways, namely through out-of-court channels (Mediation, Conciliation, Arbitration) and through the Industrial Relations Court at the District Court where the agreement is held. That the employment relationship between the Cassation Applicants / Plaintiffs and the Cassation Respondent / Defendants is bound based on the Sea Work Agreement (PKL) as regulated in article 395 KUHD article 1 number 5 and article 18 Government Regulation Number 7 Year 2000 Concerning Maritime, Article 1 number 5 Permenhub Number 84 of 2003 concerning Recruitment and Placement of Juncto Ship Crews Act Number 17 of 2008 concerning Shipping. The Sea Work Agreement is special (Lex Specialis), so the "lex specialis derogate legi generali" principle applies. The problem in this paper is about the Termination of Employment Relations unilaterally carried out by Employers (PT. Onasis Indonesia and PT. Royal Asia Maritime) to Marjan Lantang and friends (Workers) on the grounds that the work has been completed and without compensation compensation given to the The worker. This legal research uses the normative approach method. If there is a work relationship dispute between the crew and the shipping entrepreneur, the first attempt that must be made is negotiations between the employer and the worker / crew. If bipartite negotiations fail to reach a mutual agreement, the disputing parties can submit their claims to the Industrial Relations Court at the local District Court, where the company is domiciled. . The author's research results indicate that there was a mistake in the Decision of the Supreme Court Judges' Decision, especially in determining the type of Work Agreement made between Employers and Workers.